Presence of bone marrow micro‐metastases in stage I‐III colon cancer patients is associated with worse disease‐free and overall survival. (12th April 2017) - Viehl, Carsten T.; Weixler, Benjamin; Guller, Ulrich; Dell‐Kuster, Salome; Rosenthal, Rachel; Ramser, Michaela; Banz, Vanessa; Langer, Igor; Terracciano, Luigi; Sauter, Guido; Oertli, Daniel; Zuber, Markus
Abstract: The prognostic significance of bone marrow micro‐metastases (BMM) in colon cancer patients remains unclear. We conducted a prospective cohort study with long‐term follow‐up to evaluate the relevance of BMM as a prognostic factor for disease free (DFS) and overall survival (OS) in stage I‐III colon cancer patients. In this prospective multicenter cohort study 144 stage I‐III colon cancer patients underwent bone marrow aspiration from both iliac crests prior to open oncologic resection. The bone marrow aspirates were stained with the pancytokeratin antibody A45‐B/B3 and analyzed for the presence of epithelial tumor cells. DFS and OS were analyzed using a Cox proportional hazard model and robust standard errors to account for clustering in the multicenter setting. Median overall follow‐up was 6.2 years with no losses to follow‐up, and 7.3 years in patients who survived. BMM were found in 55 (38%) patients. In total, 30 (21%) patients had disease recurrence and 56 (39%) patients died. After adjusting for known prognostic factors, BMM positive patients had a significantly worse DFS (hazard ratio [HR] 1.33; 95% confidence interval [95% CI]: 1.02‐1.73; P  = 0.037) and OS (HR 1.30; 95% CI: 1.09‐1.55; P  = 0.003) compared to BMM negative patients. Bone marrow micro‐metastases occur in over one third of stage I‐III colon cancer patients and are a significant, independent negative prognostic factor for DFS and OS. Future trials should evaluate whether node‐negative colon cancer patients with BMM benefit from adjuvant chemotherapy. Abstract : This is a prospective cohort study with long‐term follow‐up to evaluate the relevance of bone marrow micro‐metastases as a prognostic factor for disease free (DFS) and overall survival (OS) in stage I‐III colon cancer patients. Bone marrow micro‐metastases were detected in over one third of stage I‐III colon cancer patients and were identified as a significant, independent negative prognostic factor for DFS and OS.